PENGARUH LINGKUNGAN TOKO TERHADAP PEMBELIAN IMPULSIF DIMEDIASI OLEH EMOSI POSITIF - Putra, Angga Prasetya; Rahanatha, Gede Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Indonesia's economy is getting better, as well as the rate of growth of Indonesia's population that continues to increase, causing changes in people's behavior in terms of shopping. Currently shopping easily and comfortably has become the desire of the people. Miniso entered the retail industry market in Indonesia to respond to changes in people's behavior. Miniso must carry out the right strategy so that consumers feel interested and make impulse purchases at Miniso. This study aims to explain the influence of the store environment on impulsive buying behavior and positive emotions. This research was conducted in Denpasar City with the number of samples taken as many as 108 respondents with a questionnaire tool. The sample was determined using a non-probability sampling model with purposive sampling technique. The data analysis technique used was path analysis with the help of the SPSS for windows program. The results of the analysis show that all hypotheses are accepted. The store environment has a positive and significant effect on Impulsive Purchases, the store environment has a positive and significant effect on positive emotions, positive emotions have a positive effect on impulsive buying and positive emotions are able to mediate the influence of the store environment on impulsive purchases